The Classroom Impact of Trained Special Needs Education Teachers in Selected Schools: An Evaluation Study - Yuwono, Imam; Okech, John Baptist (Frontiers in Education, 2021)
This study sought to find out factors that influence special needs education trained teachers’ performance in class. It was conducted between January and June 2019, involving a target population which comprised 3 government universal primary schools, with a total of 94 teachers and 2,386 learners. Study samples were selected, involving special needs education teachers (N = 73) and LwDs and OSNs (N = 30). Purposive sampling method was used to choose the required samples. A descriptive study design, involving qualitative approach was used. Open ended questionnaires and interview guides were used for collecting data on the critical role that teachers play in supporting LwDs and OSNs who experience barriers to learning under inclusive setting. One of the findings reveals that class size poses a serious challenge to teachers who are not well trained when they have LwDs and OSNs in large classes. Another finding indicates that teachers face challenges with the way the curriculum is designed—posing challenge to them on how to best handle it. It is also found that teachers face challenge to manage the average class number (teacher-learner ratio). It is also found that class room environment, resources and implementation of policies on education for LwDs and OSNs have both direct and indirect influence on the teachers’ impact in class. Basing on the findings, recommendations were made that: relevant authorities should increase support for teacher training and retraining for LwDs and OSNs. That curriculum modification should be done regularly. Classroom environments need regular improvement to be more disability friendly. Lastly, implementation of policies on disabilities and other special needs should be carried out on regular basis.